An international field study of the EORTC QLQ-PR25: A questionnaire for assessing the health-related quality of life of patients with prostate cancer - (:unkn) unknown (ELSEVIER SCI LTD, 2008)
Aim: To evaluate the psychometrics of the EORTC QLQ-PR25, a questionnaire assessing the health-related quality of life of prostate cancer patients. Methods: The QLQ-PR25 and the QLQ-C30 were administered to 642 prostate cancer patients from 13 countries treated with curative or palliative intent. The QLQ-PR25 assesses urinary, bowel and sexual symptoms and functioning, and the side-effects of hormonal treatment. Results: Five hundred and nine patients were available for the final analysis. Multitrait scaling analyses confirmed the hypothesised scale structure of the QLQ-PR25. Internal consistency reliability was good (coefficient alpha = 0.70-0.86) for the urinary symptoms and sexual function scales, but lower for the bowel function and side-effects of hormonal treatment scales (alpha < 0.70). The module discriminated clearly between clinically distinct patient subgroups, and was responsive to changes in health status over time. Conclusion: In general, the QLQ-PR25 demonstrates acceptable psychometric properties and clinical validity. Some caution should be used in interpreting the bowel function and side-effects of hormonal therapy scales; results can be reported at the individual item and scale level. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Prostate cancer; Quality of life; Patient-reported outcome; Questionnaire; Bladder function; Urinary function; Sexuality; EUROPEAN-ORGANIZATION; INDEX; MEN